Development of a material based on hydroxyapatite and aluminosilicate zeolites with a binding agent for the formation of bioactive coatings - V.M. Skachkov; E.A. Bogdanova; S.A. Bibanaeva; A.G. Shirokova (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
The hardened composite material with a porous structure was obtained by mechanochemical synthesis of nanostructured hydroxyapatite synthesized by precipitation from an aqueous solution with reinforcing additives of zirconium dioxide and silicic acid. Food gelatin is used as a binder. The influence of the phase composition on physico-chemical properties of coatings (adhesive strength, microhardness, specific surface area, microstructure) is estimated. It has been established that the use of composite material together with gelatin as a part of a bioactive coating makes it possible to increase its hardness and adhesive strength. A patent application has been filed for the developed bioactive coatings based on nanoscale hydroxyapatite and biogenic elements with a binding agent. The composition of the dry mixture based on hydroxyapatite has been developed, which ensures a long shelf life without negative consequences and creates simple transportation conditions. Dilution of the dry mixture with distilled water gives a suspension that is convenient to use for coating implants of any configuration.